1996
DOI: 10.1016/0006-8993(96)00389-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of GO/NO-GO discrimination and response selection — a PET study in man

Abstract: The purpose of this study was to identify the functional fields activated in relation to the NO-GO decision. Nine healthy subjects participated in the study which consisted of two test positron emission tomography (PET) scans (GO/NO-GO task and response selection task) and one control scan. In the response selection task, subjects were asked to flex their thumb of the right hand when a light emitting diode (LED) placed 60 cm from their eyes turned on red and to flex their index finger of the right hand when LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
91
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 40 publications
15
91
0
2
Order By: Relevance
“…Behaviorally, all seem to share a common ground of cognitive interference, response conflict, and cognitive set shifting. Moreover, functional neuroimaging studies have shown that the areas activated by both the Stroop and the go-no go tasks overlap to a great extent, most notably in the middle dorsolateral and medial prefrontal cortex as well as in the posterior parietal cortex 15,16 . This pattern is remarkably similar to the one we found for the TMT.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviorally, all seem to share a common ground of cognitive interference, response conflict, and cognitive set shifting. Moreover, functional neuroimaging studies have shown that the areas activated by both the Stroop and the go-no go tasks overlap to a great extent, most notably in the middle dorsolateral and medial prefrontal cortex as well as in the posterior parietal cortex 15,16 . This pattern is remarkably similar to the one we found for the TMT.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we have shown that patients with the diagnosis of borderline and antisocial personality disorder (which is associated with lack of impulse control) activate more widespread prefrontal and temporal cortical areas than healthy controls in the Go/No-go task (Völlm et al, 2004), a neuropsychological task requiring behavioral inhibition (Casey et al, 1997). The Go/No-go task has been widely used as a cognitive activation paradigm with normal volunteers, and it produces consistent prefrontal activation (Horn et al, 2003;Völlm et al, 2004;Rubia et al, 2003;Anderson et al, 2002;Menon et al, 2001;Liddle et al, 2001;Kawashima et al, 1996). The lateral orbitofrontal cortex (OFC), particularly on the right, is a common area activated by No-go compared with Go conditions in these studies and appears to be specifically involved in the inhibition of responses (Aron et al, 2003;Rubia et al, 2003;Menon et al, 2001;Liddle et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This association has been argued most extensively in the context of the P300, an event-related potential (ERP) elicited by infrequent events. Neuroimaging studies [Grasby et al, 1993;Jonides et al, 1993;Cohen et al, 1994;McCarthy et al, 1994;Casey et al, 1995;Smith et al, 1995;Kawashima et al, 1996;Casey et al, 1997] together with physiological studies in monkeys [Niki, 1974;Mishkin and Manning, 1978;Goldman-Rakic, 1987;Fuster, 1988;Yajeya and Fuster, 1988] have largely focused on the involvement of frontal regions in higher cognitive processes such as working memory and inhibitory control. These studies provide better spatial resolution than do electrophysiology studies and suggest that different regions within prefrontal cortex are associated with different types of processing.…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide better spatial resolution than do electrophysiology studies and suggest that different regions within prefrontal cortex are associated with different types of processing. For example, dorsolateral prefrontal cortex has been implicated in working memory [Goldman-Rakic, 1987;Fuster, 1988;Cohen et al, 1994;McCarthy et al, 1994;Smith et al, 1995], while more ventral regions of prefrontal cortex have been implicated in the suppression of prepotent responses as in the go/no-go task [Kawashima et al, 1996;Casey et al, 1997;Konishi et al, 1999]. Few imaging studies have examined the effects of manipulating target probability on these presumed prefrontal functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation